Pengaruh Kadar Air Biji Kopi Liberika Tungkal Komposit (Coffea liberica L.) Dalam Penyimpanan Terhadap Serangan Araecerus fasciculatus (De geer) - Tika Wahyuni; Araz Meilin; Nasamsir Nasamsir (Universitas Batanghari, 2022)
This study aims to determine the level of damage to coffee beans in storage at different seed moisture content caused by the pest A. fasciculatus. The research was carried out at the Basic Laboratory of the Faculty of Agriculture, Batanghari University, Jambi, from August to November 2021. Liberika coffee beans came from the Mekar Jaya II farmer group in Parit Lapis, Betara, Tanjung Jabung Barat. The study used a one-factor completely randomized design (CRD) with the treatment being tested for differences in water content including: k0 = (control) 100 liberica coffee beans, 10.7% moisture content without A. fasciculatus insects, k1 = 100 liberica coffee beans, water content 10.7 % + 10 A. fasciculatus insects, k2= 100 liberica coffee beans, 11.4% moisture content + 10 A. fasciculatus insects, and k3= 100 liberica coffee beans, 15.1% moisture content + 10 A. fasciculatus insects, each treatment was repeated as much as 8 times. The parameters observed were the characteristics of the coffee bean defect value, increase in moisture content, change in weight from the beginning to the end of the study, temperature and humidity. Data analysis used variance analysis (analysis of variance), if the treatment was significantly different, it was continued with the Duncan New Multiple Range Test (DNMRT) at the level of 5%. The results of the analysis showed that the best treatment was at k1 (10.7% moisture content) with the lowest damage level of 30.00%. It can be concluded that, the higher the moisture content of coffee beans in storage, the higher the attack rate of A. fasciculatus